Transfer of learning with an application to the physics of positron emission tomography - Aryal, Bijaya (Kansas State University, 2007)
A series of teaching activities using physical models was developed to present some portions of physics of Positron Emission Tomography (PET) and investigate students’ understanding and transfer of learning in physics to a medical technology. A teaching interview protocol consistent with a qualitative research methodology was developed and administered to the students enrolled in an algebra-based introductory level physics course. 16 students participated in individual interviews and another 21 students participated in the group sessions. The major objectives of the teaching interviews were to investigate students’ transfer of physics learning from their prior experiences to the provided physical models, from one model to the other and from the models to the PET problems. The study adapted phenomenological research methodology in analyzing students’ use of cognitive resources and cognitive strategies during knowledge construction and reconstruction. A resource based transfer model framed under the cognitive theory of learning and consistent with contemporary views of transfer was used to describe the transfer of physics learning. Results of the study indicated both appropriate and inappropriate use of the students’ prior conceptual resources in novel contexts. Scaffolding and questioning were found to be effective in activating appropriate and suppressing the inappropriate resources. The physical models used as analogies were found useful in transferring physics learning to understand image construction in PET. Positive transfer was possible when the models were introduced in an appropriate sequence. The results of the study indicate the occurrence of three types of non-scaffolded transfer – spontaneous, semi spontaneous and non-spontaneous. The research found connections between sequencing of hints and phrasing of information in activating students’ different conceptual resources. A qualitative investigation based on Vygotsky’s Zone of Proximal Development (ZPD) has been completed in two contexts – one involving an instructor and the other involving peers. Significant expansion of the students’ ZPD occurred through peer interaction. The results indicate that the appropriate sequencing of learning activities and group interactions can promote learning. Additional research in transfer of physics learning from macroscopic phenomena to microscopic phenomena are warranted by the conclusions of this work.
Keywords: Transfer; Physical models; Positron emission tomography; Physics, General (0605)